The genus Semicerura (Collembola; Isotomidae) in Asia - Potapov, Mikhail; Xie, Zhijing; Kuprin, Alexander; Sun, Xin (Zootaxa, 2020)
Two new species, Semicerura bryophila sp. nov. and S. draconis sp. nov., are described from the Far East of Russia and north-eastern part of China. S. goryshini Martynova, 1969 is redescribed based on the type material and fresh materials from China and South Korea. The holotype of S. bishopi Maynard, 1951 (eastern areas of the U.S.A.) was studied and commented on. Taxonomic remarks to s-chaetotaxy and the labium of the genus are given.